Modernising government the way forward. - Organisation for Economic Co-operation and Development; ProQuest (Firm) (Paris, France : OECD, 2005)
This book takes stock of the past two decades of public sector modernization in OECD countries. These years have witnessed an influx of new ideas and initiatives but how have these new ideas worked in practice? This report assesses failures and successes and identifies the challenges ahead. It examines certain selected key public management policy levers of reform such as: making government more responsive, transparent and accessible, instilling a performance approach in the public sector, changing accountability and control systems, facilitating reallocation and restructuring, organizing and motivating public servants, and integrating a market approach.--Publisher's description.
Open government -- Enhancing public sector performance -- Modernising accountability and control -- Reallocation and restructuring: the heavy machinery of reform -- The use of market-type mechanisms to provide government services -- Organising and motivating public servants: modernising public employment -- Modernisation: context, lessons, and challenges.
Includes bibliographical references (p. 207-216).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Public administration -- OECD countries; Organizational change -- OECD countries; Transparency in government -- OECD countries; Administrative agencies -- OECD countries -- Reorganization; Public-private sector cooperation -- OECD countries; Civil service reform -- OECD countries; OECD countries -- Politics and government; Electronic books